Potential Modulation of Gut Microbiota by Phytochemicals in Managing Noncommunicable Diseases - Nawawi, Rizki Andini (Biomedical Journal of Indonesia, 2025)
Noncommunicable diseases, such as hypertension and type 2 diabetes, remain a leading cause of death worldwide, especially in low- and middle-income countries. Recent research trends revealed possible involvement of the gut microbiota in the pathogenesis of these noncommunicable diseases. This article provides a review of recent research trends on the human gut microbiota’s involvement in hypertension and type 2 diabetes, and the potential of its modulation by natural products. Several mechanisms are proposed to explain how the gut microbiota contributes to the development of hypertension and type 2 diabetes, one of which is by changes in short-chain fatty acids (SCFAs) production. Phytochemicals targeting modulation of the gut microbiota and SCFAs production may show potential in prevention and therapy of hypertension and diabetes. This may be achieved by affecting the composition of the gut microbiota itself and by modulating the microbiota’s metabolic pathways, such as by stimulating synthesis of SCFAs. However, future studies are still needed considering the complexity of factors affecting gut microbiota, as well as the need to develop reproducible methods in studying the gut microbiota and its metabolites in order to further elucidate the role of gut microbiota in health and disease, in order to achieve optimal benefits and better clinical outcomes.